Community-Acquired Pneumonia and Empyema Caused by Citrobacter koseri in an Immunocompetent Patient - Miguel Angel Ariza-Prota; Ana Pando-Sandoval; Marta García-Clemente; Ramón Fernández; Pere Casan (Case Reports in Pulmonology)
Citrobacter species, belonging to the family Enterobacteriaceae, are environmental organisms commonly found in soil, water, and the intestinal tracts of animals and humans. Citrobacter koseri is known to be an uncommon but serious cause of both sporadic and epidemic septicemia and meningitis in neonates and young infants. Most cases reported have occurred in immunocompromised hosts. The infections caused by Citrobacter are difficult to treat with usual broad spectrum antibiotics owing to rapid generation of mutants and have been associated with high death rates in the past. We believe this is the first case described in the literature of a community-acquired pneumonia and empyema caused by Citrobacter koseri in an immunocompetent adult patient.